An 8-week resistance training protocol is effective in adapting quadriceps but not patellar tendon shear modulus measured by Shear Wave Elastography - Mannarino, P.; da Matta, T. T.; de Oliveira, L. F. (PLOS ONE, 2019)
Habitual loading and resistance training (RT) can lead to changes in muscle and tendon morphology as well as in its mechanical properties which can be measured by Shear Wave Elastography (SWE) technique. The objective of this study was to analyze the Vastus Lateralis (VL) and patellar tendon (PT) mechanical properties adaptations to an 8-week RT protocol using SWE. We submitted 15 untrained health young men to an 8-week RT directed for knee extensor mechanism. VL and PT shear modulus (µ) were assessed pre and post intervention with SWE. PT thickness (PTT), VL muscle thickness (VL MT) and knee extension torque (KT) were also measure pre and post intervention to ensure the RT efficiency. Significant increases were observed in VL MT and KT (pre = 2.40 ± 0.40 cm and post = 2.63 ± 0.35 cm, p = 0.0111, and pre = 294.66 ± 73.98 Nm and post = 338.93 ± 76.39 Nm, p = 0.005, respectively). The 8-week RT was also effective in promoting VL µ adaptations (pre = 4.87 ± 1.38 kPa and post = 9.08.12 ± 1.86 kPa, p = 0.0105), but not in significantly affecting PT µ (pre = 78.85 ± 7.37 kPa and post = 66.41 ± 7.25 kPa, p = 0.1287) nor PTT (baseline = 0.364 ± 0.053 cm and post = 0.368 ± 0.046 cm, p = 0.71). The present study showed that an 8-week resistance training protocol was effective in adapting VL µ but not PT µ. Further investigation should be conducted with special attention to longer interventions, to possible PT differential individual responsiveness and to the muscle-tendon resting state tension environment.